Optical absorbers based on strong interference in ultra-thin films - Kats, Mikhail A.; Capasso, Federico (Laser & photonics reviews, 2016)
Optical absorbers find uses in a wide array of applications across the electromagnetic spectrum, including photovoltaic and photochemical cells, photodetectors, optical filters, stealth technology, and thermal light sources. Recent efforts have sought to reduce the footprint of optical absorbers, conventionally based on graded structures or Fabry‐Perot‐type cavities, by using emerging concepts in plasmonics, metamaterials, and metasurfaces. Unfortunately, these new absorber designs require patterning on subwavelength length scales, and are therefore impractical for many large‐scale optical and optoelectronic devices. In this article, we summarize recent progress in the development of optical absorbers based on lossy films with thicknesses significantly smaller than the incident optical wavelength. These structures have a small footprint and require no nanoscale patterning. We outline the theoretical foundation of these absorbers based on “ultra‐thin‐film interference”, including the concepts of loss‐induced phase shifts and critical coupling, and then review several applications, including ultra‐thin color coatings, decorative photovoltaics, high‐efficiency photochemical cells, and infrared scene generators. Ultra‐thin optical absorbers are desired for many applications across the electromagnetic spectrum, including solar energy harvesting, photodetectors, optical filters, stealth technology, and thermal light sources. This review summarizes recent progress in the development of optical absorbers based on lossy films with thicknesses significantly smaller than the incident optical wavelength. The basic theory governing ultra‐thin‐film absorbers is discussed, along with application examples, including color coatings, decorative photovoltaics, photochemical cells, and infrared scene generators.